What is 'effective' CPD for contemporary physical education teachers? A Deweyan framework. Issue 7 (3rd October 2017) - Armour, Kathleen; Quennerstedt, Mikael; Chambers, Fiona; Makopoulou, Kyriaki
ABSTRACT: It is widely argued that continuing professional development (CPD) for physical education (PE) teachers is important, yet questions remain about 'effective' CPD. We consider these questions afresh from a Deweyan perspective. An overview of the CPD/PE-CPD literature reveals conflicting positions on teachers as learners. Considering the nature of contemporary PE, and the learning needs of teachers, we argue that a different model of PE-CPD is required to reflect the dynamic nature of contemporary practice. We propose John Dewey's classic concept of 'education as growth' to underpin a new conceptual framework for the design, delivery and evaluation of PE-CPD. We argue that 'effective' PE-CPD will not be found in formal policies, structures and processes, however, well-intentioned, unless it (i) focuses on the dazzling complexity of the learning process, (ii) prioritises context and contemporary challenges; (iii) bridges research/theory–practice in innovative ways; and (iv) nurtures the career-long growth of PE teachers.